2013
DOI: 10.1038/ncb2698
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPa controls acquisition and maintenance of adult haematopoietic stem cell quiescence

Abstract: Summary In blood, transcription factor C/EBPa is essential for myeloid differentiation and has been implicated in regulating self-renewal of fetal liver (FL) hematopoietic stem cells (HSCs). However, its function in adult HSCs has remained unknown. Here, using an inducible knockout model we found that C/EBPa deficient adult HSCs underwent a pronounced expansion with enhanced proliferation, characteristics resembling FL HSCs. Consistently, transcription profiling of C/EBPa deficient HSCs revealed a gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 41 publications
7
113
1
Order By: Relevance
“…At the HSC stage, C/EBPα acts to prime HSCs for differentiation along the myeloid lineage via DNA binding to regulatory regions of genes induced during differentiation (16). Although conditional Cebpa knockout mice do not develop disease, the loss of Cebpa in adult HSCs leads to an increased number of functional and proliferative HSCs (15,17) and loss of HSC pool maintenance in serial transplantations (16). Cebpa expression is required for AML disease initiation by the oncogene MLL-ENL but not for disease maintenance (18).…”
Section: Introductionmentioning
confidence: 99%
“…At the HSC stage, C/EBPα acts to prime HSCs for differentiation along the myeloid lineage via DNA binding to regulatory regions of genes induced during differentiation (16). Although conditional Cebpa knockout mice do not develop disease, the loss of Cebpa in adult HSCs leads to an increased number of functional and proliferative HSCs (15,17) and loss of HSC pool maintenance in serial transplantations (16). Cebpa expression is required for AML disease initiation by the oncogene MLL-ENL but not for disease maintenance (18).…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPα also controls fetal liver HSC self-renewal as C/EBPα -/-HSCs show increased competitive repopulation activity in transplanted mice (Zhang et al, 2004). Very recently, using a conditional knockout mouse, it has been shown that C/EBPα is essential for the formation and maintenance of adult HSCs (Ye et al, 2013).…”
Section: Ccaat/enhancer-binding Protein Alphamentioning
confidence: 99%
“…TLR4 activation and ligands are elevated in patients with diabetic (48,49). TLR4 activation in myeloid cells results in suppression of CEBPA and its target genes (50), while in HSPCs, low-dose LPS, absence of CEBPA, and streptozotocininduced diabetes are associated with an expanded longterm hematopoietic stem cell population (51)(52)(53). Together, these data suggest that examining the connection between chronic TLR4 activation in diabetes and its consequences for Cebpa expression and myeloid maturation may be important.…”
Section: Discussionmentioning
confidence: 93%